Variation of hardness, microstructure, and Laves phase distribution in direct laser deposited alloy 718 cuboids. (5th April 2017) - Stevens, Erica L.; Toman, Jakub; To, Albert C.; Chmielus, Markus
Abstract: Property anisotropy and its unpredictability in direct laser-deposited material is a drawback to this additive manufacturing method. In this study, direct laser deposition was used to build three-dimensional cuboids of Ni-based superalloy 718, which were examined with microscopy, and analyzed for hardness trends with contour mapping. Secondary electron and backscatter electron contrast imaging were used in conjunction with electron backscatter diffraction to understand microstructure. It is found that hardness decreased with increasing height and linear energy used during deposition. Also, the hardness of the inner hatching was higher than the outer contour, in both planar and cross-sectional surfaces. After an examination of grain structure and phase distribution, it is proposed that the hardness trends are caused by a combination of detrimental Laves phase and strengthening γ ″ phase distribution. Graphical abstract: Highlights: Alloy 718 cuboids were deposited by DLD additive manufacturing. EBSD/microhardness were mapped to assess structure/property variation. An explanation for hardness variation using Laves phase distribution is developed. Area percent and statistical analysis are performed for Laves phase at melt pool boundaries.